Health Trends among 9/11 Responders from 2011–2021: A Review of World Trade Center Health Program Statistics. Issue 5 (2nd October 2021) - Smith, Erin; Holmes, Lisa; Larkin, Brigid
Abstract: Introduction: In a single day, the September 11, 2001 US terrorist attacks (9/11) killed nearly 3, 000 people, including 412 first responders. More than 91, 000 responders were exposed to a range of hazards during the recovery and clean-up operation that followed. Various health programs track the on-going health effects of 9/11, including the World Trade Center (WTC) Health Program (WTCHP). The objective of this research was to review WTCHP statistics reported by the Centers for Disease Control and Prevention (CDC) to analyze health trends among enrolled responders as the 20-year anniversary of the terrorist attacks approaches. Methods: The WTCHP statistics reported by the CDC were analyzed to identify health trends among enrolled responders from 2011 through 2021. Statistics for non-responders were excluded. Results: A total of 80, 745 responders were enrolled in the WTCHP as of March 2021: 62, 773 were classified as general responders; 17, 023 were Fire Department of New York (FDNY) responders; and 989 were Pentagon and Shanksville responders. Of the total responders in the program, 3, 439 are now deceased. Just under 40% of responders with certified health issues were aged 45-64 and 83% were male. The top three certified conditions among enrolled responders were: aerodigestive disorders; cancer; and mental ill health. The top ten certified cancers have remained the same over the last five years, however, leukemia has now overtaken colon and bladder cancer as the 20-year anniversary approaches. Compared to the general population, 9/11 first responders had a higher rate of all cancers combined, as well as higher rates of prostate cancer, thyroid cancer, and leukemia. Discussion: Trends in these program statistics should be viewed with some caution. While certain illnesses have been linked with exposure to the WTC site, differences in age, sex, ethnicity, smoking status, and other factors between exposed and unexposed groups should also be considered. Increased rates of some illnesses among this cohort may be associated with heightened surveillance rather than an actual increase in disease. Still, cancer in general, as well as lung disease, heart disease, and posttraumatic stress disorder (PTSD), seem to be increasing among 9/11 responders, even now close to 20 years later. Conclusion: Responders should continue to avail themselves of the health care and monitoring offered through programs like the WTCHP.